Evaluation of Hepatoprotective Potential of Polyherbal Preparations in CCl4-Induced Hepatotoxicity in Mice - Rayhana Begum; Sonia Akther Papia; Mst Marium Begum; Hongbin Wang; Rubaba Karim; Rebeka Sultana; Priyanka Rani Das; Taslima Begum; Md. Ragibul Islam; Nargis Manwar; Md. Sohanur Rahman (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Polyherbal formulations (PLFs) have been widely used for liver protection, treatment for hepatic dysfunction, and regeneration. They can also enhance appetite and protect the gastrointestinal tract from injury. In spite of the prevalent use, there is a need of scientific evidence on their effectiveness and safety. The objective of the present study was to assess the hepatoprotective effect of polyherbal formulations (commercially available in Bangladesh namely Heptaliv, Holyliv, Icturn, and J-deenar) in CCl4-induced hepatotoxicity in mice. Methods. In this study, Swiss albino mice were treated for 7 days with distilled water or PLFs (2.6 and 5.2 ml/kg body weight/day, per os.) followed by single subcutaneous injection of CCl4 (1 ml/kg body weight, diluted with olive oil in 1 : 1 ratio) on day 8. Twenty-four hours after CCl4 administration, the mice were monitored for the effects of PLFs on liver morphology, biochemical parameters including serum aspartate transaminase (AST), serum alanine transaminase (ALT), alkaline phosphatase (ALP), and total bilirubin. Phenobarbitone-induced sleeping time and histopathology changes in liver tissues were also monitored. Results. CCl4 administration caused significant hepatotoxicity as evidenced by marked elevation in AST, ALT, ALP, and total bilirubin. Phenobarbitone-induced sleeping time and infiltration of inflammatory cells and centrizonal necrosis on histological examination of liver demonstrated hepatic injury after CCl4 administration. However, the administration of Icturn and J-deenar polyherbal formulations at the higher dose significantly decreased the levels of AST, ALT, ALP, and total bilirubin. Moreover, pentobarbitone-induced sleeping time and histopathological analysis also revealed significant improvement as result of treatment with formulations Icturn and J-deenar. Conclusion. Our results confirmed that polyherbal formulations (Icturn and J-deenar) can significantly prevent CCl4-induced hepatotoxicity in mice, demonstrating their protective effect for liver.